(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study aims to determine the effect of service quality on customer loyalty with customer satisfaction as a mediating variable at Jambe Asri ATV Batubulan Gianyar. The population in this study were all customers who bought services at Jambe Asri ATV, namely 3,791. The sample in the study was 97 people. The data analysis technique used in this study is the validity test, reliability test, validity test and sobel test. From the research results it can be seen that: (1) Service quality has a positive and significant effect on customer loyalty (2) Service quality has a positive and significant effect on customer satisfaction (3) Customer satisfaction has a positive and significant effect on customer loyalty. (4) Satisfaction mediates the effect of service quality on customer loyalty. The advice that researchers can give is that Jambe Asri ATV Batubulan Gianyar should improve the quality of its services by improving the online booking system. This can minimize long queues of customers and speed up administrative processes for customers